Psychological well-being on housewives who have children with special needs - Berliana Putri Pertiwi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
A housewife is a woman who is married and has been given the gift of children in her marriage.  Housewives have a big role in the process of child development.  So that mothers must be understand and find out about the conditions and needs of their children, especially in taking care of children with special needs (Special Needs Children).  Therefore, this study aims to find out about how the picture of psychological well-being in housewives who have children with special needs based on aspects and factors, how about their self-acceptance, positive relationships with others, independence, purpose in life, and personal growth of the subjects used.  Then this can be supported by one or several demographic factors, social support, evaluation of life experiences, and their locus of control.  This research is qualitative research with a phenomenological approach.  The data collection technique used is the interview method.  This study uses 3 subjects as sources of information in extracting data, plus 3 secondary subjects as reinforcement of information sources from the main subject.  The data collection technique used to get the subject is the snowball sampling technique which will meet the criteria: 1) housewives who do not work, and 2) mothers aged 30 – 40 years.The results of the research that have been obtained state that the three subjects have psychological well-being based on aspects and factors of the psychological well-being. In addition, there are other influences that support the psychological well-being of the subject, namely gratitude, self-adjustment, self-concept, and regulations that exist in the three subjects.